How to be an Eliminativist - Rosenberg, Alexander (Filozoficzne Aspekty Genezy, 2022)
In the 40 years since its first promulgation, contemporary eliminativism about intentional content has secured considerable additional support in the form of both neuroscientific findings and an absence of significant counter-evidence within the now greatly expanded study of the brain and its components. This paper reports some of the most telling of these results. Three serious issues remain to be dealt with by philosophical proponents of eliminativism: claims that neuroscience’s frequent use of the word “representation” requires or presupposes that neural circuitry actually carries such content, claims that the phenomenology of first-person introspection reveals the undeniable existence of intentional content, and arguments to the effect that eliminativism is self-refuting, contradictory or pragmatically paradoxical, owing to its claim that there are no true assertions. This paper addresses these three arguments against eliminativism.